Respuesta :

Answer: Choice B (1,-2)

note: I'm assuming there is a "less than or equal to" sign as part of the given inequality, rather than a simple "less than" sign (without the "or equal to" part)

============================================

Work Shown:

Plug in x = -2 and y = 4 from the point (x,y) = (-2, 4). Then simplify. If you get a true statement, then this is a solution point

[tex]y - 4x \le -6[/tex]

[tex]4 - 4*(-2) \le -6[/tex]

[tex]4 + 8 \le -6[/tex]

[tex]12 \le -6[/tex]

This statement is false. The value 12 is not to the left of -6 on the number line, nor is 12 equal to -6. So (x,y) = (-2,4) is not a solution

-------------

Plug in x = 1 and y = -2

[tex]y - 4x \le -6[/tex]

[tex]-2 - 4*(1) \le -6[/tex]

[tex]-2 - 4 \le -6[/tex]

[tex]-6 \le -6[/tex]

This statement is true, but only if the inequality sign is a "less than or equal to" sign. Otherwise, the statement is false because -6 cannot be smaller than itself.

-------------

Plug in x = 1 and y = 3

[tex]y - 4x \le -6[/tex]

[tex]3 - 4*(1) \le -6[/tex]

[tex]3 - 4 \le -6[/tex]

[tex]-1 \le -6[/tex]

Like choice A, this is false. So (x,y) = (1,3) is not a solution

-------------

Plug in x = 2 and y = 3

[tex]y - 4x \le -6[/tex]

[tex]3 - 4*(2) \le -6[/tex]

[tex]3 - 8 \le -6[/tex]

[tex]-5 \le -6[/tex]

We end up with another false statement. So (x,y) = (2,3) isn't a solution either.